Smoking and breast cancer risk by race/ethnicity and oestrogen and progesterone receptor status: the Multiethnic Cohort (MEC) study - Gram, Inger T (Int J Epidemiol, 2019)
BACKGROUND: The purpose of this study was to examine if the smoking-related higher breast cancer risk was similar for the five race/ethnicity groups in the Multiethnic Cohort (MEC) study and by oestrogen (ER) and progesterone (PR) receptor status. METHODS: From 1993 to 2013, we followed 67 313 women who were enrolled in the MEC study at 45–75 years of age. We identified breast cancer cases and tumour receptor status via linkage to the Hawaii and California Surveillance, Epidemiology and End Results Program cancer registries through December 2013. We used Cox proportional hazards regression to estimate multivariable-adjusted hazard ratios with 95% confidence intervals (CI). RESULTS: During a mean follow-up of 16.7 years, we identified 4230 incident, invasive breast cancer cases. Compared with parous never smokers, parous ever smokers who had smoked more than 5 years before their first live childbirth had a higher risk of breast cancer overall of 31% (95% CI: 1.14–1.51). This higher risk was 51% (95% CI: 1.05–2.16) for African Americans, 66% (95% CI: 1.10–2.50) for Native Hawaiians, 42% (95% CI: 1.13–1.78) for Whites, 37% (95% CI: 1.17–1.61) for ER-positive (ER+) tumours and 33% (95% CI: 1.11–1.59) for PR+ tumours. No difference was suggested by racial/ethnic groups (P(heterogeneity) = 0.15) or tumour receptor status (P(heterogeneity) = 0.60 by ER status and 0.95 by PR status). CONCLUSIONS: We find that the higher breast cancer risk related to smoking is similar across racial/ethnic groups and by ER and PR status, indicating that breast cancer should be considered as a smoking-related cancer.